THE MAIN PROBLEMS OF FINANCING THE CINEMATOGRAPHY DEVELOPMENT IN UKRAINE - Kinal , Nadiya (Socio-economic relations in the digital society, 2021)
The aim of the article is to study the peculiarities of financing the sphere of cinema in Ukraine and substantiate the directions of development of Ukrainian cinema in modern conditions. The historical development of the film industry in Ukraine is analyzed. In the context of the forms of implementation of state functions on the trend of Ukrainian cinema, the development of cinema in 2014—2019 is presented. In addition, statistical data on state funding of film production and analyzed certain aspects of the current state of Ukrainian cinema. Also, the author’s view on the main problems of the domestic film industry of today is presented and the foreign experience of regulation of financial support of development of the sphere of cinematography is analyzed and the directions of its perspective application in Ukraine are substantiated. Certain models of cinema regulation are proposed in order to ensure the best possible development of Ukrainian cinema and attract private investment. The methodological approach for the development of material and technical base and improvement of art education is substantiated. Therefore, the recommendations arising from the analysis of Ukrainian and foreign experience are proposed to ensure the development of the Ukrainian film sphere, promoting national consciousness, patriotic feelings and strengthening national identity as a consolidating basis for state development and resistance to external geopolitical challenges. In order to provoke effective development of the cinematography in Ukraine it is grounded such recommendations: further increase of state funding of Ukrainian cinematography; development of the legal framework in the field of cinema; providing preferential tax terms for companies interested in film production; the interest of Ukrainian filmmakers in watching domestic cinema through the dissemination of information; promoting the expansion of the network of cinemas (in particular, in settlements that do not have access to cinemas); state support of Ukrainian projects at international film festivals and promotion of cooperation of Ukrainian directors with European colleagues; increase funding for art education for high-quality education of future new movie stars, which in the long run can bring world fame to Ukrainian cinema and develop the field of culture at the international level; attracting private investment for the development of cinema in Ukraine.
Keywords: cinematography; film industry; film sphere; financing; box office; film festival; financial resources